2021
DOI: 10.1029/2021gl093098
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Characteristics of Giant Undulations During Geomagnetic Storms

Abstract: In this letter, the statistical characteristics of the structures of giant undulations (GUs) during geomagnetic storms are studied for the first time, based on aurora images during 2005–2019. The GUs mainly occur within ∼4 h following the beginning of the storm main phase and finish in ±4 h around the storm peak. The most interesting feature is that the anti‐sunward edge of GUs is quasi‐stable (18–19 h MLT) during their lifetime. The latitudinal amplitudes of GUs (AGU) peak at 200–300 km while the azimuthal wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(35 citation statements)
references
References 41 publications
1
34
0
Order By: Relevance
“…Following the method proposed by Anderson et al (2008), the ion density dropping region with the maximum gradient near the auroral equatorial boundary was extracted to be the ionospheric footprint of the PP region (e.g., Anderson et al, 2008;Weygand et al, 2021;, as shown in Figure 1. For each GU image in the database of Zhou et al (2021), the upper and lower boundaries of the PP region (indicated by the vertical blue and red lines in the top panel of Figure 1, respectively) are identified to form the PP database in this study when there are simultaneous ion density measurements with high quality (i.e., quality flag 1 in the RPA data).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Following the method proposed by Anderson et al (2008), the ion density dropping region with the maximum gradient near the auroral equatorial boundary was extracted to be the ionospheric footprint of the PP region (e.g., Anderson et al, 2008;Weygand et al, 2021;, as shown in Figure 1. For each GU image in the database of Zhou et al (2021), the upper and lower boundaries of the PP region (indicated by the vertical blue and red lines in the top panel of Figure 1, respectively) are identified to form the PP database in this study when there are simultaneous ion density measurements with high quality (i.e., quality flag 1 in the RPA data).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the SSUSI and RPA on each DMSP satellite made nearly simultaneous measurements along the trajectory. A database of GUs has been constructed in our previous work (Zhou et al., 2021). In this study, the corresponding PP parameters were extracted from the RPA measurements.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…During substorm activities, the density irregularities at nightside PBLs can be associated with fast plasma injections (Morioka & Oya, 1996; Thomas et al., 2021), which may drive inductive electric fields and cause the density irregularities subsequently (Morioka & Oya, 1996). In particular, these injections can trigger the sawtooth‐shaped giant undulations of the plasmapause surface (He et al., 2020) and may be responsible for density irregularities in PBLs at dusk and post‐dusk sectors (Zhou et al., 2021).…”
Section: Discussionmentioning
confidence: 99%